Regional, Ethnic and Age-Sexual Features of Acute Coronary Syndromes in Fergana Region - Karimov, Ulugbek; Mamasoliev, Nematjon; Tajibaeva, Laylo; Usmonov, Burkhonjon (RA Journal of Applied Research, 2021)
Background. Cardiovascular diseases (CVDs) are a group of disorders of the heart and blood vessels. The most important behavioral risk factors for heart disease and stroke are unhealthy diet, physical inactivity, tobacco use and harmful use of alcohol. Exposure to behavioral risk factors can manifest in humans as high blood pressure, high blood glucose, high blood lipids, and overweight and obesity. Methods. The research was conducted on hospitalized male and female patients aged from 26 to 88 years with suspicion of the acute coronary syndrome (ACS) at the time of admission to the hospital in the Andijan and Fergana Valley. Overall, 653 patients were examined. The study included a retrospective and prospective part with the inclusion of patients with ACS. Findings. Fairly wide prevalence of ACS was revealed in terms of their epidemiological characteristics in both gender groups, as well as in different age groups. It is necessary to improve the work on "life-saving prevention" among the population in relation to an adequate assessment of the symptoms of CVD in patients and the implementation of medical recommendations for optimizing prevention, early detection and treatment of ACS.